CAF hierarchy driven by pancreatic cancer cell p53-status creates a pro-metastatic and chemoresistant environment via perlecan - Vennin, Claire; Mélénec, Pauline; Rouet, Romain; Nobis, Max; Cazet, Aurélie S.; Murphy, Kendelle J.; Herrmann, David; Reed, Daniel A.; Lucas, Morghan C.; Warren, Sean C.; Elgundi, Zehra; Pinese, Mark; et al. (Nature communications, 2019)
Heterogeneous subtypes of cancer-associated fibroblasts (CAFs) coexist within pancreatic cancer tissues and can both promote and restrain disease progression. Here, we interrogate how cancer cells harboring distinct alterations in p53 manipulate CAFs. We reveal the existence of a p53-driven hierarchy, where cancer cells with a gain-of-function (GOF) mutant p53 educate a dominant population of CAFs that establish a pro-metastatic environment for GOF and null p53 cancer cells alike. We also demonstrate that CAFs educated by null p53 cancer cells may be reprogrammed by either GOF mutant p53 cells or their CAFs. We identify perlecan as a key component of this pro-metastatic environment. Using intravital imaging, we observe that these dominant CAFs delay cancer cell response to chemotherapy. Lastly, we reveal that depleting perlecan in the stroma combined with chemotherapy prolongs mouse survival, supporting it as a potential target for anti-stromal therapies in pancreatic cancer. Subtypes of cancer associated fibroblasts can both promote and suppress tumorigenesis. Here, the authors investigate how p53 status in pancreatic cancer cells affects their interaction with cancer associated fibroblasts, and report perlecan as a mediator of the pro-metastatic environment.